Anatomic Basis of Echocardiographic Diagnosis - Chan, Kwan-Leung.; Veinot, John P.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
Echocardiography is a versatile imaging modality that can be performed at the bedside to promptly provide reliable anatomic and functional information useful for the management of patients with heart disease. There have been many technological advances in echocardiography, resulting in an improvement in image quality and new insights into cardiac mechanics. In order to fully appreciate and utilize these advances, it is crucial to have an in-depth understanding of the cardiac anatomy and how this relates to echocardiography. For instance, mitral valve repair is now the surgical method of choice for the treatment of patients with degenerative mitral valve disease and severe mitral regurgitation, but it requires excellent understanding of the mitral valvular and subvalvular anatomy to allow selection of appropriate patients and the detection of complications associated with the surgical repair. Anatomic Basis of Echocardiographic Diagnosis provides a systematic approach in the clinical application of echocardiography based on a comprehensive understanding of cardiac anatomy and pathology. Covered within are discussions on general cardiac anatomy, normal variants and the orientation of the heart in the thorax and its effect on the acoustic windows. Later sections cover diseases that affect various cardiac structures, such as the valves, the myocardium and the pericardium, and examine specific clinical settings in which echocardiography plays a pivotal role in the differential diagnosis and clinical management. Examples that incorporate echocardiographic images with pathologic correlations are included in every chapter, evidence of the importance of collaborative effort between echocardiographer and pathologist. Also included are many 3D echocardiographic images to highlight normal and abnormal findings, as well as numerous pathologic images providing anatomic correlates of the echocardiographic findings. The nearly 700 images have been carefully selected to illustrate key findings, and thus the book can serve equally well as an atlas and should be a useful resource to sonographers, cardiology trainees, internists and cardiologists.
Keywords: Medicine; Diagnosis, Ultrasonic; Internal medicine; Cardiology; Medicine & Public Health; Cardiology; Ultrasound; Internal Medicine